The Dating of Pindaric Odes by Comparison - Hans A. Pohlsander (Greek, Roman, and Byzantine Studies, 2002)
<!--StartFragment--> Similarities of diction and thought are not adequate evidence to establish dates for Pindar’s odes, as is shown by the examples of Nemean 3 and 11 and Isthmian 4. <!--EndFragment-->